Microwave-assisted synthesis and photocatalytic properties of sulphur and platinum modified TiO2 nanofibers. Issue 1 (9th March 2015) - Drunka, R; Grabis, J; Jankovica, Dz; Krumina, A; Rasmane, Dz
Abstract: In the present work formation of active TiO2 nanofibers in microwave synthesis and their modification with platinum were studied. Mixture of anatase and rutile nanopowder and 10M KOH solution were used as raw materials. Microwave assisted synthesis method permitted to obtain TiO2 nanofibres with a diameter of 10nm and a specific surface area up to 40.2 m 2 /g. In order to modify TiO2 nanofibers with platinum it was stirred in H2 PtCl6 solution and illuminated with UV irradiation or reduced with sodium boronhydride. To modify titania with sulphur and prepare co-doped nanofibers platinum doped samples were extra treated in hydrogen sulphide atmosphere. Photocatalytic activity was determined by degradation of the methylene blue (MB) solution under UV and visible light irradiation. The obtained samples showed higher photocatalytic activity with respect to pure TiO2 nanofibers. The doped TiO2 nanofibers were appropriate for degradation of harmful organic compounds.